Сындарлы оқыту – оқу мен оқытудағы жетістіктердің тиімді стратегиясы - Жаныбекова, Ж.К. (My University, 2016)
Young children may not be able to record their understanding in writing but may do so in discussion with the teacher or with each other.
Keywords: discussion; understanding; readiness; incapable; fixation